ANALISA REDUPLIKASI & MODIFIKASI INTERNAL DALAM BAHASA ARAB DAN BAHASA INDONESIA - Rifki, Ahmad; Mudlofir, Ali; Muflihah, Muflihah (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
No in-depth analysis comprehensively compares Arabic and Indonesian reduplication and internal modification phenomena. Therefore, this study aims to fill this knowledge gap and present a deeper understanding of how these two languages use reduplication and internal modification in word formation and their morphological consequences. The main problem to be solved is how this phenomenon operates in both languages, what the differences and similarities are, and how its use affects the structure and meaning of words in the linguistic context of each language. This research uses descriptive qualitative methods, using data analysis as library research. The research results reveal that both languages use reduplication and internal modification to form words with diverse meanings. Although there are differences in how the two languages implement this phenomenon, they also share basic concepts about how repetition and internal modifications in word morphology can produce variations in meaning.